Real-time calcium uptake monitoring of a single renal cancer cell based on an all-solid-state potentiometric microsensor - Zhai, Jiali; Wang, Wenting; Wu, Shuang; Yu, Tianxi; Xiang, Chongjun; Li, Yue; Lin, Chunhua; Zhao, Guangtao (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: In addition to many cellular processes, Ca2+ is also involved in tumor initiation, progression, angiogenesis, and metastasis. The development of new tools for single-cell Ca2+ measurement could open a new avenue for cancer therapy. Methods: The all-solid-state calcium ion-selective microelectrode (Ca2+-ISμE) based on carbon fiber modified with PEDOT (PSS) as solid-contact was developed in this work, and the characteristics of the Ca2+-ISμE have also been investigated. Results: The Ca2+-ISμE exhibits a stable Nernstian response in CaCl2 solutions in the active range of 1.0 × 10−8 - 3.1 × 10−3 M with a low detection limit of 8.9 × 10−9 M. The Ca2+-ISμE can be connected to a patch clamp to fabricate a single-cell analysis platform for in vivo calcium monitoring of a single renal carcinoma cell. The calcium signal decreased significantly (8.6 ± 3.2 mV, n = 3) with severe fluctuations of 5.9 ± 1.8 mV when the concentration of K+ in the tumor microenvironment is up to 20 mM. Discussion: The results indicate a severe cell response of a single renal carcinoma cell under high K+ stimuli. The detection system could also be used for single-cell analysis of other ions by changing different ion-selective membranes with high temporal resolution.